Experimental Study of K-Band Broadband Antenna Array Using Artificial Inhomogeneous Dielectric Structures - Anton M. Aleksandrin; Yury P. Salomatov (Известия высших учебных заведений России: Радиоэлектроника)
Introduction. As a result of the extensive development of broadband communication in the millimetre wave band, there has arisen a need for antenna systems with a high level of directivity and compact dimensions, capable of operating across wide frequency ranges. However, at present, few engineering solutions satisfy this demand.Aim. To develop and study experimentally a K-band antenna array (AR) characterized by a high aperture efficiency and compact longitudinal dimensions.Materials and methods. Computer simulations were performed using the CST Studio Suite software. Measurements were carried out using an Agilent E8363B PNA vector circuit analyzer. Radiation patterns were obtained by the method of near-field scanning.Results. A K-band broadband antenna array configuration operating over the 18…26 GHz range was pro-posed. It was found that the period of the array equals 2.25 wavelengths at the highest operating frequency. In order to suppress grating lobes, an additional layer consisting of artificial inhomogeneous dielectric lenses was used. The dielectric material consisted of thin curly layers of sheet polyethylene terephthalate. Additionally, a hybrid configuration of feeding network was proposed, in which one part of the network was developed by means of printed two-wire lines, while the other part was achieved by means of rectangular waveguides. The proposed antenna array demonstrates VSWR of less than 2 and an aperture efficiency above 0.5, side and diffractive lobe levels not exceed –12 in the 18…26 GHz range. The total thickness of the configuration equals 50 mm or 4.3λmin. In order to ensure the compactness of the AR for wideband frequency applications, the thickness of the system can be reduced to 2.5λmin by excluding the waveguide part.Conclusion. When compared with existing solutions, the proposed antenna has a simpler feed network, which yields better matching. High aperture efficiency is achieved in the wide frequency range by means of inhomogeneous dielectric lenses.